STRATEGI PERTAHANAN AMERIKA SERIKAT DALAM MERESPONS ANCAMAN TIONGKOK DI INDO-PASIFIK PADA MASA KEPEMIMPINAN JOE BIDEN - Marianne Olivia Delanova; Fadillah, Firman (Indonesian Journal of International Relations, 2023)
This study aims to explain the geopolitical dynamics that are developing in the Indo-Pacific and examine how during Joe Biden's leadership he formed his defense approach to protect interests and maintain stability in the Indo- Pacific region. By using qualitative methods and data collection techniques, namely interviews, analysis of internet sources, and related literature. Neorealism theory according to Kenneth Waltz and Arthur Lykke's strategic concept are used. The results of the research through an analysis of and ends, ways, and means state that the US has the main strategy, namely by forming alliances and cooperation with regional countries and strengthening the strength of army personnel with joint exercises carried out with regional alliance countries. The existence of this strategy means that the US responds to China with caution.